Coordinating Complex Work: Knowledge Networks, Partner Departures, and Client Relationship Performance in a Law Firm - Briscoe, Forrest; Rogan, Michelle (Management Science, 2016)
The mobility of individual managers has long presented a problem for firms in knowledge-intensive industries. Shifting to more complex work often reduces the importance of a single individual’s knowledge for the firm’s exchange relationships because complex work requires inputs from a broader set of the firm’s members. Although complex work decreases the likelihood that a single individual can shift the exchange relationship to another firm, we propose that it increases the vulnerability of the firm’s performance to departures of those individual managers who act as coordinators of knowledge. This leads us to focus on how the internal knowledge network formed to maintain each relationship can compound or mitigate the loss of a coordinating manager. Using original data on client relationships from a law firm, we examine the effect of internal knowledge networks and lead partner departures on the performance of the relationships. Supporting our argument, we find that the negative performance effect of a lead partner departure is greater when the network has high knowledge heterogeneity and involves more experts and lower when the network has high cohesion. This paper was accepted by Jesper Sørensen, organizations.